Reconstruction of Extensive Composite Parotid Region Oncologic Defects with Immediate Facial Nerve Reconstruction Using a Chimeric Scapulodorsal Vascularized Nerve Free Flap - Mangialardi, Maria L.; Honart, Jean-Fracois; Qassemyar, Quentin; Guyon, Alice; Li, Sean S.; Benmoussa, Nadia; Beldarida, Vincent; Temam, Stéphane; Kolb, Frédéric (Journal of Reconstructive Microsurgery, 2020)
Background Cancer involving the parotid gland region may originates from parotid parenchyma itself or from locoregional organs and in rare cases, the facial nerve (FN) has to be sacrificed during tumor resection. In these cases, cancer extension often goes beyond the parotid compartment and requires extensive local resection responsible for complex multitissular defects. The goals of reconstruction may be summarized in the following two components: (1) restoration of the volumetric tissue defect and (2) FN reconstruction. The aim of this study is to describe our surgical technique and our cosmetic results using the chimeric scapulodorsal vascularized nerve (SDVN) flap to reconstruct extensive maxillofacial defects associated with FN sacrifice.Methods All patients undergone an extensive maxillofacial resection with FN sacrifice and primarily reconstructed with a SDVN flap were included. We classified the maxillofacial defects into six groups based on the type of resection. Intraoperative data including flap composition, topography of FN injury, length of nerve gap, and number of nervous anastomosis were recorded.Results Twenty-nine patients were included. Mean follow-up was 38.7 months. The harvested flaps included the SDVN combined with different components according to the defect group. A satisfactory volumetric restoration was obtained in 93% of cases. The mean number of distal nervous anastomosis was 4.5. The length of the vascularized grafted nerve ranged from 7 to 10 cm.Conclusion This is largest series presented in literature on primary FN reconstruction utilizing a vascularized nerve graft. We believe that the chimeric SDVN flap should be highly considered for these cases due to its versatility. The surgeon is able to use single donor site available soft and hard tissues components along with a vascular motor nerve graft, which offers a great length and number of distal branches, and easily matches with the extracranial FN trunk and its peripheral ramifications.
Keywords: vascularized nerve graft; facial nerve; scapulodorsal flap